2020
DOI: 10.1515/cclm-2020-0094
|View full text |Cite
|
Sign up to set email alerts
|

A hierarchical bivariate meta-analysis of diagnostic test accuracy to provide direct comparisons of immunoassays vs. indirect immunofluorescence for initial screening of connective tissue diseases

Abstract: ObjectivesTo compare indirect immunofluorescence (IIF) for antinuclear antibodies (ANA) against immunoassays (IAs) as an initial screening test for connective tissue diseases (CTDs).MethodsA systematic literature review identified cross-sectional or case-control studies reporting test accuracy data for IIF and enzyme-linked immunosorbent assays (ELISA), fluorescence enzyme immunoassay (FEIA), chemiluminescent immunoassay (CLIA) or multiplex immunoassay (MIA). The meta-analysis used hierarchical, bivariate, mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Is it time to compare solid-phase assays and automated IIF for detection of ANAs? [21][22][23]. Can solid-phase assays replace immunofluorescence for ANA screening?…”
Section: Indirect Immunofluorescence (Iif) Assays Using Hep-2 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Is it time to compare solid-phase assays and automated IIF for detection of ANAs? [21][22][23]. Can solid-phase assays replace immunofluorescence for ANA screening?…”
Section: Indirect Immunofluorescence (Iif) Assays Using Hep-2 Cellsmentioning
confidence: 99%
“…However, it is essential to take into account how the different cut-off points of the assays are chosen in order to consider a positive result, since the differences observed in the performance between assays are largely related to these. Thus, in a meta-analysis of paired studies and considering the cut-off value for HEp-2 IIF as 1:80 the sensitivity of IIF, FEIA, and CIA was 89.2%, 78.5%, and 85.9%, respectively, and the specificity was 70.9%, 93.6%, and 86.1%, respectively, for ANA-associated SARDs [22]. In contrast, studies that consider the cut-off point as the value that corresponds to a specificity of 95%, showed that HEp-2 IIF, FEIA, and CIA for ANA-associated SARDs presented similar sensitivities of 79%, 82%, and 78%, respectively [13].…”
Section: Solid-phase Assays (Spas)mentioning
confidence: 99%
“…The major drawbacks of these methods are the use of a limited number of purified or recombinant autoantigens, lack of standardization, and the prevalence of "false negative" ANA results, although some of them with questionable clinical significance. A recent meta-analysis compared IIF with solid-based immunoassays used as an initial screening method (49). No significant difference between ELISA and IIF (cut-off 1:80) was found both in terms of sensitivity and specificity.…”
Section: Ana Screen Assaymentioning
confidence: 99%
“…A recent systematic meta‐analysis demonstrated that CLIA had good specificity compared with indirect immunofluorescence in ANA testing. 31 In addition, MBA has shown certain advantages over conventional techniques, including the feasibility of high‐throughput analyses for multiple antigens, minimal labor for automation, and reduced cost of samples. 32 However, the antigen composition of the bead‐based assays also varies significantly, and issues with false‐positive results are the main concern for MBAs.…”
Section: Discussionmentioning
confidence: 99%